2021
DOI: 10.1177/15266028211010455
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Gore VBX Balloon Expandable Endoprosthesis as Bridging Stent-Graft in Branched Endovascular Aortic Repair for Thoracoabdominal Aneurysms

Abstract: Purpose Bridging stent stability is crucial for efficacy and safety of branched aortic endovascular repair (bEVAR) of thoracoabdominal aortic aneurysms (TAAAs). In this study, we assess the performance of the new Viabahn Balloon-Expandable endoprosthesis (VBX) in bEVAR. Based on our learning curve we give recommendations for a safe and effective use of the device. Materials and Methods We prospectively collected the data of patients with TAAAs undergoing bEVAR between December 2017 and December 2019. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…34 Regarding BESGs, the available experience has shown high primary patency rate achieving 100% with low endoleak and re-intervention rate. 18,35 Currently available literature has shown that both stent types can be safely and effectively applied during BEVAR, and this meta-analysis is in accordance with the primary patency and endoleak rates of the literature in both stent types. However, the role of relining and its impact on patency need further investigation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…34 Regarding BESGs, the available experience has shown high primary patency rate achieving 100% with low endoleak and re-intervention rate. 18,35 Currently available literature has shown that both stent types can be safely and effectively applied during BEVAR, and this meta-analysis is in accordance with the primary patency and endoleak rates of the literature in both stent types. However, the role of relining and its impact on patency need further investigation.…”
Section: Discussionsupporting
confidence: 86%
“…6 TV instability was defined a composite outcome used to define any death or rupture related to side branch complication, including occlusion, device migration affecting any branch, branch-related sac growth or any secondary intervention indicated to treat a branch-related complication, including endoleak, disconnection, kink, stenosis, occlusion, or rupture. 16 -18 Re-intervention was considered any secondary intervention after the completion of the main intervention that was related to TV complications.…”
Section: Methodsmentioning
confidence: 99%
“…After removing duplicates, 606 records were retrieved. Papers were screened and selected, as illustrated in Figure 1 (477 records were excluded after the title and abstract screening, 6 reports were not retrieved in full text, and 59 were excluded with reasons), resulting in 64 papers meeting our defined inclusion criteria 10,23–85 . Characteristics of the included studies are reported in Supplemental Table S1 (Supplemental Digital Content 1, http://links.lww.com/SLA/E987).…”
Section: Resultsmentioning
confidence: 99%
“…Studies (n = 64) were published between 2006 and 2021, with over 15% (n = 11, 17,2%) published in the last 3 years. 29,37,49,51,54,60,65,72,74,81,82 The majority of the studies (n = 28, 43,8%) were conducted in Europe (Italy, n = 12; Germany, n = 7; Netherlands, n = 3; Portugal, n = 1; France, n = 3; United Kingdom, n = 2) 23,[26][27][28][29]31,43,[45][46][47][48][49][50][51]54,[56][57][58][59]64,66,70,72,76,82,84 and in the USA (n = 27, 42,2%). 10,24,25,32,33,35--40,52,53,60-63,65,67,68,71,73,75,77,79,81,85 Five studies were conducted in Japan, 44,69,78,80,83 two in Brazil, 41,42 one in Canada, 74 and one in Serbia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A previous study about the employment of VBX stents in BEVAR demonstrated the existence of a learning curve to achieve the best results, and thus, reducing the risk of stent dislodgement and type Ic endoleak. 12 This subcohort assessment from the post-market, multicenter, prospective registry aims to assess the performance of the VBX stent used as a BSG for the treatment of visceral vessels during BEVAR.…”
mentioning
confidence: 99%